Rhetorical resonance: exploring potentiality through materiality and symbolicity - Lewis, Derek, author; Dunn, Thomas R., advisor; Dickinson, Greg, advisor; Ore, Janet, committee member (Colorado State University. Libraries, 2016)
Using the Mall of America in Bloomington, Minnesota, as an artifact for analysis, this thesis investigates how rhetoric and communication scholars can better understand and investigate the linkages between material objects and symbolic discourses as they pertain to the production of rhetorics. This thesis offers a theory of rhetorical resonance to guide the analysis of how multiple material and symbolic components resonate together and produce rhetorics. Building from theories of affect and ambience, rhetorical resonance offers a way for scholars to analyze the effects of materiality and symbolicity as resonant facets of the world. Additionally, this thesis proposes a resonant methodology to orient scholars in their pursuit of analyzing rhetorically resonant artifacts. Drawing from previous rhetorical work in rhetorical field methods and “being [through] there,” this thesis develops a methodology focused on building an artifact from pieces instead of accepting one thing as an entity itself. Finally, this thesis utilizes a resonant theory and methodology to analyze the Mall of America. It draws out the various pieces of the mall’s security rhetorics while focusing on how it contrasts the harshness and danger of being outside with the relative safety and comfort within the structure itself. Additionally, this thesis also analyzes how once inside, the Mall of America diverts security attention to young teens who are prohibited by the Parental Escort Policy from being alone in the mall. Overall, this thesis serves to push rhetorical theory and methodology to engage with artifacts and analyze the way material and symbolic components work together to produce rhetorics upon an audience.
Keywords: resonance; symbolicity; rhetoric; materiality